Technology Evolution in Membrane-Based CCS - José Luis Míguez; Jacobo Porteiro; Raquel Pérez-Orozco; Miguel Ángel Gómez (Energies, 2018)
In recent years, many CO2 capture technologies have been developed due to growing awareness about the importance of reducing greenhouse gas emissions. In this paper, publications from the last decade addressing this topic were analyzed, paying special attention to patent status to provide useful information for policymakers, industry, and businesses and to help determine the direction of future research. To show the most current patent activity related to carbon capture using membrane technology, we collected 2749 patent documents and 572 scientific papers. The results demonstrated that membranes are a developing field, with the number of applications growing at a steady pace, exceeding 100 applications per year in 2013 and 2014. North American assignees were the main contributors, with the greatest number of patents owned by companies such as UOP LLC, Kilimanjaro Energy Inc., and Membrane Technology and Research Inc., making up 26% of the total number of published patents. Asian countries (China, Japan, and Korea) and international offices were also important knowledge sources, providing 29% and 24% of the documents, respectively. Furthermore, this paper highlights 10 more valuable patents regarding their degree of innovation and citations, classified as Y02C 10/10 according to the Cooperative Patent Classification (CPC) criteria.